ANALYSIS OF FACTORS DETERMINING CUSTOMER LOYALTYIN BUILDING SHOPPING SATISFACTION AT A COFFEE SHOP - Muh. Husriadi; Megasari Megasari; Citra Ayu Ningsi (CV. Adiba Aisha Amira, 2025)
This research is motivated by the challenges in building loyalty coffee shop customers in the middle increasing competition​ tight and changing behavior consumers. The aim of the research is to understand factors that influence loyalty customer through experience holistic shopping, including​ quality products, services, atmosphere, social interactions, and the use of digital technology. The method used is a qualitative approach with a case study design, involving interview in-depth and observation participatory approach at several coffee shops in Kendari City. Data analysis was conducted using the Miles and Huberman model to identify themes and patterns the main results of the study showed that the consistency of coffee taste and menu variety, friendliness staff, atmosphere comfortable, meaningful social interactions, and convenience access to digital technology together to form satisfaction and loyalty customers. The implications of this research emphasize importance integration aspect products, services, environment, and technology with a personal approach to create experience sustainable and competitive customer service. Recommendations given for coffee shop managers to optimize training staff, interior design, and utilization of technology without ignore human interaction.